KOHESI GRAMATIKAL PADA CERITA PENDEK DI KORAN REPUBLIKA TAHUN 2022 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Sabilulhaq, Arina (Alegori: Jurnal Mahasiswa Pendidikan Bahasa Indonesia, 2024)
The purpose of this study is to identify and analyze grammatical cohesion in short stories from the newspaper "Republika" in the year 2022, and its implications for the teaching of the Indonesian language. The research uses a descriptive method with content analysis techniques. The findings reveal the use of grammatical cohesion in two short stories titled "Perjalanan Bapak" and "Haji Veteran" published in "Republika," totaling 334 instances. The distribution of grammatical cohesion in the findings is as follows: conjunctions 111 instances (33%), substitutions 23 instances (7%), references 158 instances (47%), and ellipsis 42 instances (13%). The research outcomes also have implications for the teaching of the Indonesian language, specifically in meeting the learning objectives KD. 3.9 and 4.9, which involve analyzing the structure and language of short story texts.Keywords: Discourse, Grammatical Cohession, Short Story